Tantangan dan Peluang Inovasi Pelayanan Publik di Era Revolusi Industri 4.0 - Almahdali, Humairah (Jurnal Studi Ilmu Sosial dan Politik, 2024)
Purpose: This article explores the challenges and opportunities of public service innovation in the Industrial Revolution 4.0 era. Methodology: The study employs a qualitative research approach that integrates literature analysis and expert interviews to explore the adoption and implementation of digital technologies in public sector services. The literature analysis involved a systematic review of academic journals, policy reports, and case studies to establish a theoretical framework and identify best practices from various regions. In parallel, in-depth interviews were conducted with experts in public policy, information technology, and digital governance to capture their insights on real-world challenges and opportunities. The qualitative approach was chosen for its ability to provide a nuanced understanding of complex phenomena, allowing for an in-depth exploration of both contextual and practical aspects of technological adoption in public services. Result: The findings reveal that digital technology enhances efficiency and transparency but faces barriers in regulation, infrastructure, and human resources. Limitation: Access to valid and up-to-date data on technology implementation in public services can be limited, especially in countries or regions that have not widely adopted technology. Articles may struggle to provide a comprehensive picture of technology implementation worldwide or even at the national level. Contribution: This study provides insights for policymakers to design technology-based public service innovation strategies.